Levomilnacipran ER 40 mg and 80 mg in patients with major depressive disorder: a phase III, randomized, double-blind, fixed-dose, placebo-controlled study - Bakish, David (Canadian Medical Association, 2014)
BACKGROUND: Major depressive disorder (MDD) is a global health concern. This study examined the efficacy, safety and tolerability of an extended-release (ER) formulation of levomilnacipran, an antidepressant approved for the treatment of MDD in adults. METHODS: This 10-week (1-week placebo run-in period, 8-week double-blind treatment, 1-week down-taper), multicentre, double-blind, placebo-controlled, parallel-group, fixed-dose study was conducted between June 2011 and March 2012. Adult outpatients (age 18–75 yr) with MDD were randomly assigned (1:1:1) to placebo or to levomilnacipran ER 40 mg/day or 80 mg/day. For primary efficacy, we analyzed the Montgomery–Åsberg Depression Rating Scale (MADRS) change from baseline to week 8 using a mixed-effects model for repeated-measures approach on the intent-to-treat (ITT) population. For secondary efficacy, we used the Sheehan Disability Scale (SDS), and for safety, we examined adverse events and laboratory, vital sign/physical and electrocardiography findings. RESULTS: The ITT population consisted of 185 patients in the placebo group, 185 in the levomilnacipran ER 40 mg/day group and 187 in the levomilnacipran ER 80 mg/day group. Study completion rates were similar among the groups (76%–83%). On MADRS change from baseline the least squares mean difference (LSMD) and 95% confidence interval (CI) versus placebo was significant for levomilnacipran ER 40 mg/day (–3.3 [−5.5 to −1.1], p = 0.003) and 80 mg/day (−3.1, [−5.3 to −1.0], p = 0.004). On SDS change from baseline the LSMD (and 95% CI) versus placebo was also significant for levomilnacipran ER 40 mg/day (−1.8, 95% [−3.6 to 0], p = 0.046) and 80 mg/day (−2.7 [−4.5 to −0.9], p = 0.003). More patients in the levomilnacipran ER than the placebo group prematurely exited the study owing to adverse events; common adverse events (≥ 5% and ≥ double the rate of placebo) were nausea, dry mouth, increased heart rate, constipation, dizziness, hyperhidrosis, urinary hesitation and erectile dysfunction. LIMITATIONS: Limitations to our study included short treatment duration and lack of an active control arm. CONCLUSION: Levomilnacipran ER at doses of 40 mg/day and 80 mg/day demonstrated efficacy on symptomatic and functional measures of MDD and was generally well tolerated in this patient population. CLINICAL TRIAL REGISTRATION: NCT01377194.